PENGARUH BUDAYA KERJA, DISIPLIN KERJA DAN K3 TERHADAP KINERJA KARYAWAN TETAP BAGIAN PRODUKSI UNIT SPINNING 2 PADA PT APAC INTI CORPORA - Ismariana, Putri; Hidayat, Wahyu; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2015)
Human resource management is one of the factors that determine the success or failure of the company. In order to determine the role and contribution of human resources in achieving success, of course necessary performance measurement. Employee performance is influenced by several factors, including the culture of work, work discipline and occupational health and safety (K3). Including employee performance degradation caused by the work culture that has not been fully implemented, the lack of discipline of employees and service to lack of K3. PT Apac Inti Corpora is a company engaged in the field of textile products such as yarn, gray fabric and denim fabric.This research aims to know and explain the influence of positive work culture, discipline of work and employee performance against K3 remains part of the production unit spinning 2 PT Apac Inti Corpora. This research is explanatory research type approach uses against 79 respondents with Incidental technique. Data collection techniques in the research using interview techniques, questionnaire and the study of librarianship. The data obtained were analyzed quantitatively using a cross-tabular analysis tools, test validity, reliability test, a simple linear regression, multiple linear regression and hypothesis testing by t-test and F-test as well as using the help application programs SPSS 20.0 for Windows.Results of the statistical analysis shows the work culture, work discipline and K3 has a positive influence on performance of employees. Seen from the calculation of the coefficients of the regression test, where the influential work of cultural 0,098, discipline working effect of 0.125, K3 and influential of 0,496. From these results it is known that the greatest influence affecting performance variable (Y) is K3 variables (X3).Advice that can be given in this research to enhance implementation of the cultural work by conducting briefings on a regular basis so that culture can be lived and practiced. Companies need to improve discipline by giving sanction expressly and reprimand for employees, whereas for the implementation of K3 enterprises need to increase socialization and simulation of safety. As well as the need for continued research by companies or parties outside the company about other free variables that can provide an additional contribution to improving the performance of employees.